The End of Law: Carl Schmitt in the Twenty-First Century - Alves da Silva, Felipe (Princípios: Revista de Filosofia (UFRN), 2022)
Resenha de Scheuerman, William E. The End of Law: Carl Schmitt in the Twenty-First Century. 2. ed.. London/New York: Rowman & Littlefield, 2020. 343 p.